2022
DOI: 10.3390/jcm11092314
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Excessive Anticoagulation and Missing Hyperinflammation in ECMO-Associated Bleeding

Abstract: Extracorporeal membrane oxygenation (ECMO) is increasingly used in carefully selected patients with cardiac or respiratory failure. However, complications are common and can be associated with worse outcomes, while data on risk factors and outcomes are inconsistent and sparse. Therefore, we sought to investigate potential risk factors and predictors of haemorrhage and adverse events during ECMO and its influence on mortality. We retrospectively reviewed all patients on ECMO support admitted to intensive care u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Comparable to literature, hemorrhage was the second most frequent complication in nearly half of the patients, which is in line with the largest meta-analysis so far, reporting any kind of hemorrhage in 40% [ 15 ]. Going into greater detail confirmed the cannulation and surgical area being the most common sites of bleeding [ 32 34 ]. However, the latter findings may be weakened by the fact that only one study reported on the use of the ELSO bleeding definition [ 23 ], despite the definition´s existence of more than 8 years.…”
Section: Discussionmentioning
confidence: 99%
“…Comparable to literature, hemorrhage was the second most frequent complication in nearly half of the patients, which is in line with the largest meta-analysis so far, reporting any kind of hemorrhage in 40% [ 15 ]. Going into greater detail confirmed the cannulation and surgical area being the most common sites of bleeding [ 32 34 ]. However, the latter findings may be weakened by the fact that only one study reported on the use of the ELSO bleeding definition [ 23 ], despite the definition´s existence of more than 8 years.…”
Section: Discussionmentioning
confidence: 99%
“…The association of hyperinflammation with the occurrence of thrombosis, and a potentially reduced risk of bleeding, has already been described in literature [ 33 , 34 ]. Moreover, the methods of systemic inflammatory response syndrome after cardiopulmonary bypass minimization are being applied in daily clinical practice [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of cardiopulmonary bypass recommendations, including the application and further development of circuit bonding and leukodepletion, use of glucocorticoids, aprotinin, complement inhibitors, etc., exist [ 35 ]. However, in the case of va-ECMO, there is a paucity of evidence on the role of inflammation, originating mostly from retrospective or animal studies [ 26 , 33 , 36 , 37 ]. Further studies are warranted to clarify the role of inflammation in the outcome of ECMO patients and determine potential therapeutic interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperinflammation may lead to a limitation of the UFH effect by decreasing antithrombin levels or increasing heparin binding to acute phase proteins [ 42 , 43 , 44 ]. A recent report on a possible association between bleeding and unintended excessive anticoagulation in ECMO patients without hyperinflammation remains to be confirmed in larger cohorts [ 13 ]. Finally, despite the extensive development of anticoagulants, ECMO pumps, oxygenators, and tubing systems, the systemic inflammatory response syndrome and distorted hemostasis remain a clinical concern.…”
Section: Inflammation Coagulation and Ecmomentioning
confidence: 99%
“…The initiation of ECMO support is associated with complex inflammatory and coagulation responses, as a reaction to the blood encountering the large artificial surface of an extracorporeal system circuit [ 12 ]. These processes may further lead to endothelial injury and disrupted microcirculation with consequent end-organ dysfunction and the need for systemic anticoagulation [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%